2017
DOI: 10.1111/ahg.12223
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Apolipoprotein E polymorphism on susceptibility of Wilson disease

Abstract: Wilson disease (WD) is an autosomal-recessive disorder caused by mutations in the ATP7B gene leading to abnormal copper deposition in liver and brain. WD manifests diverse neurological and hepatic phenotypes and different age of onset, even among the siblings, with same mutational background suggesting complex nature of the disease and involvement of other candidate genes. In that context, Apolipoprotein E (APOE) and Prion Protein (PRNP) have been proposed to be potential candidates for modifying the WD phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Even, the mean age does not vary significantly between the groups bearing different genotype of this polymorphism. This result is similar to our previous finding, where APOE variants showed an overall association with the disease (Roy et al, 2017). Besides, other studies have also reported the association of DMT1 variant with the susceptibility of the disease (Przybyłkowski et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Even, the mean age does not vary significantly between the groups bearing different genotype of this polymorphism. This result is similar to our previous finding, where APOE variants showed an overall association with the disease (Roy et al, 2017). Besides, other studies have also reported the association of DMT1 variant with the susceptibility of the disease (Przybyłkowski et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, a Copper metabolism MURR1 domain containing protein 1 (COMMD1) mutation has been associated with abnormally high urinary copper in one patient (Gupta et al, 2010). Again, we have found association of APOE and PRNP polymorphisms as modifiers of susceptibility and clinical features among Indian WD patients (Roy et al, 2017). However, all the variable clinical features of WD cannot be explained on the basis of these genes.…”
Section: Introductionmentioning
confidence: 63%
“…In vivo and cell‐based experiments have revealed that transcription of DBH may be induced by estradiol, which prompted us to investigate the distribution of allele and genotype frequencies of DBH polymorphisms among the male and female WD patients present with neurological symptoms (see Supporting information, Table S3). We did not observe any sex‐specific preponderance of any allele or genotype of the selected DBH polymorphisms.…”
Section: Resultsmentioning
confidence: 99%
“…14 Roy et al subsequently suggested that APOE and PRNP genotypes may be associated with cognitive or behavioural symptoms. 15 A whole-exome sequencing study examining genes in the ATP7B interactome suggested rare variants in ESD and INO80 might also affect phenotype. 10…”
Section: Geneticsmentioning
confidence: 99%